STUDIES ON SEED GERMINATION IN PEACH (PRUNUS PERSICA L. BATSCH) ROOTSTOCK FLORDAGUARD - BHAWNA THAKUR; HARMINDER SINGH (The Bioscan, 2015)
The highest percent seed germination (57.26), height (130.56 cm), girth (0.57cm), number of seedlings ready for grafting (46.53) and minimum duration of seed germination (16.33), mortality rate (1.9) was recorded in the scarification treatment. Irrespective of the treatments the maximum percent seed germination (22.57) , number of seedlings ready for grafting (16.68) was recorded when seeds were sown on 15th December and height (84.96 cm), girth (0.42 cm) was recorded when seeds were sown on 25th December and minimum duration of seed germination (23.62) was also recorded on 25th December. The present study revealed that vegetative parameters in terms of height, girth and number of leaves of the seedlings and root growth and survival percentage of the seedlings at the end of the experiment was found maximum when the seeds were sown after scarification on 25th December. All the growth regulators were not found to be effective for improving seed germination in peach rootstock ‘Flordaguard’.